2017
DOI: 10.1177/0003489417696510
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report and Systematic Review of Eosinophilic Angiocentric Fibrosis of the Paranasal Sinuses

Abstract: This review suggests that an endoscopic approach to EAF tumor is a viable option, frequently yielding complete resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
(88 reference statements)
0
10
0
Order By: Relevance
“…Contrary to the view that majority of EAF cases lie on the spectrum of IgG4‐RD, fewer than half (six of 20, 30%) of the cases assessed in this study met the 2019 ACR/EULAR classification criteria for IgG4‐RD. Seven cases 7,12–14,18,19 (including one from the present paper) did not meet the initial entry criterion of characteristic organ involvement. Of the remaining seven cases, a further five cases 2,3,7,11,20 were noted to lack sufficient data, including serum IgG4 levels and/or IHC investigations for IgG4.…”
Section: Discussionmentioning
confidence: 85%
“…Contrary to the view that majority of EAF cases lie on the spectrum of IgG4‐RD, fewer than half (six of 20, 30%) of the cases assessed in this study met the 2019 ACR/EULAR classification criteria for IgG4‐RD. Seven cases 7,12–14,18,19 (including one from the present paper) did not meet the initial entry criterion of characteristic organ involvement. Of the remaining seven cases, a further five cases 2,3,7,11,20 were noted to lack sufficient data, including serum IgG4 levels and/or IHC investigations for IgG4.…”
Section: Discussionmentioning
confidence: 85%
“…Diffuse inflammatory lesions involving the orbit or sinus take longer to treat, recur more frequently, and often require multiple operations. Studies have shown that 62% of sinus EAF cases undergo complete resection, with a recurrence rate of 20% [ 20 ]. Therefore, this disease requires close follow-up and observation and timely evaluation of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Few EAF cases have been reported in the literature with a full evaluation of IgG4-RSD criteria [ 5 , 7 , 11 , 22 , 24 ] and only a few of them have met the criteria to be considered part of IgG4-RSD. Some studies have hypothesized that the similarity between EAF and IgG4-RSD is more striking in the early stages of the disease, while in the later stages it becomes more difficult to show both IgG4 + plasma cells in the perivascular infiltrate and high IgG4 serum levels [ 9 , 10 ]. Table 2 summarizes the previously reported cases of EAF and their association with IgG4 serum levels.…”
Section: Discussionmentioning
confidence: 99%
“…EAF clinically presents as a tumefactive lesion, more often occurring in the upper respiratory tract, the sinonasal region, and the orbit, frequently causing progressive and prolonged airway obstruction [ 3 , 4 , 5 , 6 , 7 , 8 ]. Septal disease with the lateral wall, paranasal sinuses, and subglottic area involvement may also be seen [ 9 , 10 , 11 , 12 ]. Until now, to the best of our knowledge, just a single case of cutaneous involvement has been described [ 13 ] as an asymptomatic nodule.…”
Section: Introductionmentioning
confidence: 99%